2016
DOI: 10.1097/mrr.0000000000000153
|View full text |Cite
|
Sign up to set email alerts
|

The Mini-BESTest: a review of psychometric properties

Abstract: The Mini-Balance Evaluation Systems Test (Mini-BESTest) has been identified as the most comprehensive balance measure for community-dwelling adults and elderly individuals. It can be used to assess balance impairments in several other conditions, mainly Parkinson's disease and stroke. Despite increasing use of the Mini-BESTest since it was first published 5 years ago, no systematic review synthesizing its psychometric properties is available. The aim of this study was to provide a comprehensive review of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
55
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 39 publications
(143 reference statements)
15
55
0
1
Order By: Relevance
“…22 Since the first publication of the Mini-BESTest in 2011, many studies have examined the psychometric properties of the Mini-BESTest, providing support for its reliability and validity in individuals with Parkinson’s disease and stroke. 23 Tsang et al (2013) reported the Mini-BESTest to be an instrument with high reliability and validity with no floor or ceiling effects in community dwelling stroke survivors. 14 Only few studies have compared the responsiveness of the Mini-BESTest with standard scales such as the BBS, 13,24 and to the best of our knowledge none have compared the performance of both instruments in individuals with chronic stroke especially in the context of walking recovery.…”
Section: Discussionmentioning
confidence: 99%
“…22 Since the first publication of the Mini-BESTest in 2011, many studies have examined the psychometric properties of the Mini-BESTest, providing support for its reliability and validity in individuals with Parkinson’s disease and stroke. 23 Tsang et al (2013) reported the Mini-BESTest to be an instrument with high reliability and validity with no floor or ceiling effects in community dwelling stroke survivors. 14 Only few studies have compared the responsiveness of the Mini-BESTest with standard scales such as the BBS, 13,24 and to the best of our knowledge none have compared the performance of both instruments in individuals with chronic stroke especially in the context of walking recovery.…”
Section: Discussionmentioning
confidence: 99%
“…The Mini-BESTest and the 10MWT are found to be reliable and valid in persons with PD [9,26,27,32,33,40]. The revised version of the ST used in the present study still needs to be examined with regard to reliability and validity for persons with PD.…”
Section: Discussionmentioning
confidence: 81%
“…In individuals with PD the Mini-BESTest has excellent inter-rater reliability with an interclass correlation (ICC) ranging between 0.91 and 0.99 [9,26] as well as excellent test-retest reliability (ICC=0.92 to 0.98 [9,26]. The test is valid [27] and can predict fallers among persons with PD [9,28].…”
Section: Measurementsmentioning
confidence: 98%
“…The reliability of the Mini-BESTest, both inter-rater and test-retest reliability, is reported to be excellent, with ICCs of 0.98 (0.97–0.99) and 0.96 (0.94–0.99), respectively [ 30 ]. The content validity is also reported to be high [ 24 , 31 ]. The minimal clinically important difference (MCID) is 4 points [ 30 ].…”
Section: Methodsmentioning
confidence: 99%